SiP-heterocycles derived from a bulky phosphanylsilylene - Wang, Chenfeng; Su, Ming-Der; Fang, Zijie; Zhou, Jiahao; Zhang, Haoqi; Li, Xiaodi; Zuo, Darui; Zhang, Zheng-Feng; Li, Yan (Chemical communications (Cambridge, England), 2023)
Bis(1-adamantyl)phosphanylsilylene 1 was reacted with ArC&z.tbd;CR (Ar = Ph, 4-iPr-C 6 H 4 , 3-F-C 6 H 4 ; R = H, Ph) at 80 °C under microwave irradiation to afford fluorescence-active SiP-heterocycles 3a-d , which may undergo unique isomerizations starting from silirene intermediates. Moreover, the treatment of 1 with AdC&z.tbd;P furnished a heavy congener of cyclopentadiene ( 4 ), whose formation involves cleavage of the Si( ii )-P bond that is rarely observed in silylene chemistry. A new bis(1-adamantyl)phosphanylsilylene was synthesized and reacted with alkynes and a phosphaalkyne to furnish different Si-P heterocyclic complexes.